Systematic Literature Review on Human Resource Management Effect on Organization Performance - Metasebia Adula; Shashi Kant; Zerihun Ayenew Birbirsa (Annals of Human Resource Management Research, 2022)
Purpose: The current study is the outcome of a thorough evaluation of the literature on functionalism in human resource management as it relates to organizational performance. It examines the role of human resource management and examines various issues with human resource management in firms in such situations. Research Methodology: The theoretical underpinnings were established through a systematic review and subsequent thematic content analysis of the literature, including reports from published literature and research papers. These were critically examined, and the best-matching documents were carefully chosen for inclusion to reach a conclusion. Results: The results emphasize the need for HR managers to implement innovative strategies for empowering staff to navigate a rapidly changing environment and reach their full potential. A conceptual framework is proposed to engage stakeholders, address challenges, and foster a positive organizational culture, while identifying opportunities and solutions during times of crisis. Conclusions: This review highlights the growing importance of evaluative commentary in human resource management research, the ongoing debate between corrective and evaluative reviews, and the need to improve writing skills among scholars to advance the field Limitations: Risks of bias such as selection bias, insufficient blinding, attrition bias, and selective outcome reporting may be among the limitations. Contributions: This study provides a systematic review of HRM practices' impact on organizational performance, identifies key strategies that enhance employee performance, and proposes a framework for future research in the field. Novelty: Research novelty is a new concept that might result in new knowledge or contribute to already-existing knowledge.